2014
DOI: 10.1371/journal.pgen.1004612
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis RRP6L1 and RRP6L2 Function in FLOWERING LOCUS C Silencing via Regulation of Antisense RNA Synthesis

Abstract: The exosome complex functions in RNA metabolism and transcriptional gene silencing. Here, we report that mutations of two Arabidopsis genes encoding nuclear exosome components AtRRP6L1 and AtRRP6L2, cause de-repression of the main flowering repressor FLOWERING LOCUS C (FLC) and thus delay flowering in early-flowering Arabidopsis ecotypes. AtRRP6L mutations affect the expression of known FLC regulatory antisense (AS) RNAs AS I and II, and cause an increase in Histone3 K4 trimethylation (H3K4me3) at FLC. AtRRP6L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 79 publications
2
65
0
Order By: Relevance
“…At1g54440 encodes AtRRP6L1, a nuclear subunit that associates with the exosome core complex. AtRRP6L1 has been reported to function in the processing of long non-coding RNAs (lncRNAs) involved in epigenetic silencing (Shin and Chekanova, 2014). It also participates in the retention of Pol V transcribed scaffold lncRNAs through a pathway independent of exosome-mediated RNA degradation (Zhang et al, 2014a).…”
Section: Resultsmentioning
confidence: 99%
“…At1g54440 encodes AtRRP6L1, a nuclear subunit that associates with the exosome core complex. AtRRP6L1 has been reported to function in the processing of long non-coding RNAs (lncRNAs) involved in epigenetic silencing (Shin and Chekanova, 2014). It also participates in the retention of Pol V transcribed scaffold lncRNAs through a pathway independent of exosome-mediated RNA degradation (Zhang et al, 2014a).…”
Section: Resultsmentioning
confidence: 99%
“…Probably, the repression of distal COOLAIR transcription, the degradation products of distal forms of COOLAIR, or the degradation process itself, is the signal for recruiting FLD to FLC chromatin and decreases H3K4 dimethylation levels. Interestingly, recent data showed that exosome components RRP6L-1 and -2 are essential for repression of FLC through modulating different COOLAIR expression [56].…”
Section: Function Of Coolair In the Autonomous Pathwaymentioning
confidence: 99%
“…In Arabidopsis, lncRNAs such as COLDAIR (cold-assisted intronic non-coding RNA) and COOLAIR (cold induced long antisense intragenic RNA) have been demonstrated to mediate chromatin modifying activities in transcriptional silencing of FLC during veRNAlization [10,11]. Another antisense lncRNA, ASL, a nonpolyadenylated transcript, has been discovered and is implicated in epigenetic silencing of FLC [12]. LincRNAs such as AT4 and IPS1 (INDUCED BY PHOSPHATE STARVATION1) act as decoys of miRNAs by a target mimicry mechanism.…”
Section: Introductionmentioning
confidence: 99%